Preparation and characterization of novel hybrid of chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Journal of Biomedical Materials Research Part A, 2006)
The utilization of biopolymers and the development of organic-inorganic hybrids are ever increasing interest of material science researchers around the globe for various applications. The present attempt is intended to prepare nanocomposites of lactic acid grafted chitosan and layered silicates. Nanocomposites were prepared by dissolving chitosan and dispersing sodium montmorillonite in aqueous solution of L-lactic acid with subsequent heating and film casting. They were characterized by conventional techniques such as Fourier transform infrared spectroscopy, X-ray diffractometry, thermogravimetric analysis, energy dispersive X-ray spectroscopy, and elemental analysis. The results from polar optical and transmission electron microscopic measurements are also discussed. Sorption behavior of samples has been followed by measuring swelling degree and contact angle. The films have shown enhanced hydrophilicity when compared with polylactic acid (PLA). Issues on the interactions of polycationic chitosan with clay are also discussed. It is observed that nanocomposites are exhibiting better thermal and physical properties than neat chitosang-LA and PLA. (c) 2006 Wiley Periodicals, Inc.
Keywords: Chitosan; contact angle; graft copolymerization; Nanocomposites; polylactic acid; water absorption

Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Enhancement of thermal stability and phase relaxation behavior of chitosan dissolved in aqueous l-lactic acid: using `silver nanoparticles' as nano filler - Rana, V. K.; Pandey, Asutosh K.; Singh, Raj Pal; Kumar, B.; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Chitosan films with various compositions of silver nanoparticles were prepared by solution casting with an aqueous solution of chitosan and l-lactic acid. The chitosan/Ag nanocomposites were characterized by wide angle Xray diffraction (WAXD) and UV-vis spectroscopy. An analysis of the surface topography and size of the Ag nanoparticles (<= 100 nm) were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. Thermogravimetric analysis (TGA/DTA) confirmed the increase in thermal stability with increasing Ag nanoparticle content in the nanocomposites. Dynamic thermal analysis (DMA) was used to examine the phase relaxation behavior of chitosan and its nanocomposites. The conductivity of chitosan/Ag nanocomposites was considered with respect to the frequency. Contact angle measurements were used to characterize the surface twistability, surface cleanliness, and hydrophilic/hydrophobic nature of the surface.
Keywords: Chitosan; conductivity; contact angle; relaxation; silver nanoparticles

Preparation and characterization of novel hybrid of bio-assisted mineralized Zn-Al layered double hydroxides using chitosan as a template - Depan, Dilip; Singh, Raj Pal (Journal of Applied Polymer Science, 2010)
The purpose of this study was to prepare and characterize a novel nanohybrid prepared from the template-assisted mineralization of Zn-Al Layered Double Hydroxide (LDH) onto the surface of Chitosan (CSI), with an emphasis on morphology, biocompatibitity, and its use as an efficient drug carrier agent. The as prepared LDH is highly crystalline, with platelet-like morphology and curved tactoids when nucleated onto the surface of CSI. Our results indicate that the -OH and -NH functional moieties on CSI can direct an ordered structure of LDH, due to the electrostatic interaction between biopolymer and inorganic lamellae. We have been successful to intercalate an anti-inflammatory drug, Sodium Ibuprofen (Ibu), into LDH, through conventional coprecipitation method. LDHs are endowed with great potential for delivery vector because their stacked layers lead to safe reservation of biofunctional molecules or genes, and their ion exchangeability and solubility in acidic media (pH < 4) give rise to the controlled release of drug molecules. According to the cell-growth studies, LDHs are found as cell viable up to the concentration of 500 mu g/mL. This study reveals that LDH not only plays a role of a biocompatible-delivery matrix but also facilitates a significant increase in the delivery efficiency. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115:3636-3644,2010
Keywords: bio-assisted mineralization; cell-growth studies; Chitosan; drug delivery systems; layered double hydroxides

Ultrasound-triggered release of ibuprofen from a chitosan-mesoporous silica composite - a novel approach for controlled drug release - Depan, Dilip; Saikia, Lakshi; Singh, Raj Pal (Macromolecular Symposia, 2010)
In this work, an attempt was made to synthesize a novel Chitosan-Mesoporous silica (CS-MS) hybrid composite to design a drug delivery system based on ultrasound triggered stimuli-responsive smart release. The in-vitro drug release properties of both the Mesoporous Silica (MS) and Chitosan (CS) hybrids were investigated. Ibuprofen (Ibu) was used as a model drug. The results from powder X-Ray diffraction (XRD) patterns, and BET N(2) adsorption isotherms exhibited that MS can accommodate drug molecules into the lumen of the channels and pores. Drug release, stimulated by temperature and pH of the release media was also investigated. We studied the Ultrasound (US) triggered release of Ibu in a simulated body fluid (pH 7.4). The results exhibited that US can be used as a non-invasive technique for drug release from polymeric materials. The enhancing effect of ultrasound on drug release is due to the Cavitation effect, without causing any significant destruction on the polymer morphology.
4th International Symposium on Macro-and Supramolecular Architectures and Materials, Dusseldorf, GERMANY, SEP 07-11, 2008
Keywords: Chitosan; drug delivery systems; ibuprofen; Mesoporous silica; Ultrasound

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Glycolic acid-g-chitosan-gold nanoflower nanocomposite scaffolds for drug delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This paper reports a simple novel method for the synthesis of flower like gold nanoparticle (three dimensional branched nanoparticle) with >30 tips, under controlled temperature condition. Formation of flower like Au nanoparticle was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and gold nanoflower (AuNF) in controlled drug delivery and tissue engineering applications. The drug loaded novel nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Grafting of glycolic acid to the chitosan and incorporation of drug were evaluated by Fourier transform infrared spectroscopy (FTIR). The nanohybrid scaffolds were found to be stable towards the pH of the medium. The cell viability study shows that prepared nanohybrid scaffolds are biocompatible. Gold nanoflowers were found to control the drug release rate in the buffer solution (pH 7.4). Therefore, for the glycolic acid grafted chitosan based system, gold nanoflowers are the viable additive for drug delivery. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Drug delivery system; Glycolic acid grafting; Gold nanoflower; Nanocomposite

Glycolic acid-g-chitosan-Pt-Fe3O4 nanoparticles nanohybrid scaffold for tissue engineering and drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This work presents the potential use of novel nanohybrid based on chitosan-g-glycolic acid and Pt-Fe3O4 composite nanoparticles in drug delivery and tissue engineering applications. The Pt-Fe3O4 hybrid nanoparticles are prepared by thermal decomposition of H2PtCl6 center dot 6H(2)O at high temperature. The prepared nanoparticles were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and physical property measurement system (PPMS). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and Pt-Fe3O4 hybrid nanoparticles in controlled drug delivery applications. The drug loaded nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Drug loading and grafting of chitosan was characterized by Fourier transform infrared spectroscopy (FTIR). The cell proliferation also shows that the prepared nanohybrids are biocompatible. The nanohybrid was found to be stable regardless of pH of the medium. Therefore, Pt-Fe3O4 hybrid nanoparticles are viable additive for sustained drug delivery and it could be applied in the field of biomedical. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Chitosan; drug delivery; Glycolic acid grafting; Pt-Fe3O4 hybrid nanoparticle

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis